SPIRITUAL AND SCIENTIFIC HERITAGE OF QAMUSI ALLAMA ABU BAKR MUHAMMAD ZAKARIA AR-RAZI (Scientific journal of the Fergana State University, 2024)
This article analyzes the spiritual and scientific legacy of Abu Bakr Zakariyy al-Razi, a famous thinker of the Middle Ages and one of the encyclopedic scholars.Human health and the field of science related to it - medicine has become one of the relevant and highly noteworthy fields in all eras of human society. As a result of this, great discoveries have been made in this field of the development of society to this day, leading treatment tools and methods. creation is highlighted.